Implementasi Metode Weighted Product (WP) Dalam Pengambilan Keputusan Kepala Laboraturium Komputer : Sistem Informasi Pemilihan Kepala Labor Komputer Menggunakan Metode Weighted Product Berbasis Web - Jannah, Miftahul; Khelvin Ovela Putra (LPPM Universitas Dinamika Bangsa, 2023)
In a university that has an informatics profile, a computer laboratory is needed. The laboratory is also an important facility for practicing the application of the theory that has been learned. Therefore, a laboratory head is needed who has competence in managing the laboratory so that learning is more effective. However, what happened was that the head of the laboratory who was elected did not have competence because the selection system was subjective so that it could not solve the existing problems. Therefore we need a decision support system in selecting the head of the computer laboratory. The method used in making this decision is the weighted product (WP) because this method can solve multiple withdrawals and easier calculations, and the time for calculations is shorter than other decision-making methods. after ranking with existing calculations, the results obtained from the calculation of the Weighted Product (WP) method with the highest value are in alternative A2 with the name Gery Mivano, S, T with a value of 0.374910. These results can make it easier for academics to make decisions for heads of computer laboratories who have competence in solving existing laboratory problems so that practical learning in computer laboratories can be more effective. Keywords: Weighted Product, laboratory, subjective